Evaluating of Iranian Legal System in the Field of Tobacco Products with Emphasizing Human Right to Health - Bagheri, Farahnaz; Khosravi, Hassan (Journal of History Culture and Art Research, 2017)
Right to health is one of the fundamental human rights in international human right system. This right possessed a stable position in various treaties and international conventions. Based on this right, everyone has the right to reach the highest standard of physical and mental health which includes all medical services, public sanitation, enough food, suitable accommodation, healthy atmosphere of work and healthy environment. Governments are obliged to promote the right to health whether in citizens or non-citizens. Effective restriction on tobacco products requires national, local and international cooperation. In international level, the universal convention of World Health Organization has the regulations related to control of tobacco products business. Accordingly, Iran has joined to the convention thus its articles are binding inside the country. In addition to this regulation, producing and distributing tobacco products in Iran have followed by some principals and rules including: I) Producing of every type of tobacco product gained monopoly by government, II) The necessity of inserting logo and health warning messages on pocket, III) All of tobacco products must be packed in pockets with serial number and the particular label of Iran tobacco products, IV) Limitation of selling tobacco products to under aged people (under 18).